Inovasi Pembelajaran Siswa di Tengah Pandemic Covid -19 (Studi Kasus SD Negeri 33 Cempa Kabupaten Pinrang) - Hasmawati Ishak; Abdul Halim Wedda; ilham ilham (Universitas Kanjuruhan Malang, 2022)
The purpose of this research is to identify innovations that can be used in the online learning process during the Covid-19 pandemic. The method used in this research is an exploratory qualitative approach, using a phenomenological approach, collecting data obtained from various credible references (eg journals, books, etc.) and then processing the data by the author. The results showed that the use of the E-Learning method in managing learning during the COVID-19 pandemic was very appropriate to be applied at SD N 33 Cempa, Pinrang Regency. The E-learning method as a technological innovation has procedures that do not depend on place and time, E-learning in the form of blended learning is a student learning innovation that is appropriate and well implemented at SD N 33 Cempa, Pinrang Regency during the current covid-19 pandemic.